2014
DOI: 10.1017/thg.2014.54
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Covariance Between Central Corneal Thickness and Anterior Chamber Volume: A Hungarian Twin Study

Abstract: Background: Few, and inconsistent, studies have showed high heritability of some parameters of the anterior segment of the eye; however, no heritability of anterior chamber volume (ACV) has been reported, and no study has been performed to investigate the correlation between the ACV and central corneal thickness (CCT). Methods: Anterior segment measurements (Pentacam, Oculus) were obtained from 220 eyes of 110 adult Hungarian twins (41 monozygotic and 14 same-sex dizygotic pairs; 80% women; age 48.6 ± 15.5 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…The CCT phenotype is a highly heritable trait based on twin studies [65][66][67]. There is, however, no single genetic determination for CCT [68].…”
Section: Genetic Associationsmentioning
confidence: 99%
“…The CCT phenotype is a highly heritable trait based on twin studies [65][66][67]. There is, however, no single genetic determination for CCT [68].…”
Section: Genetic Associationsmentioning
confidence: 99%
“…Next is Hegedűs et al's (2014) sociological assessment of what advantages being a twin brings, followed by Molnár et al's (2014) case study of multiple valve disease found in triplets. Finally, Oniszczenko and Dragan's (2014) review of twin research in Poland is followed by an original article by Toth et al (2014), assessing the genetic covariance between central corneal thickness and anterior chamber volume. The special issue is concluded by Vlckova et al's (2014) gene expression study highlighting that the most modern forms of twin research are present in the region and conducted to the highest standards.…”
mentioning
confidence: 99%